PEMBUATAN ASAM OKSALAT DARI PELEPAH KELAPA SAWIT MENGGUNAKAN METODE PELEBURAN ALKALI - Seri Maulina, M Hidayat Hasibuan (Jurnal Teknik Kimia USU, 2016)
Palm frond is one of the solid waste from oil palm plantations which contains lignocellulose namely cellulose, hemicellulose, and lignin. Cellulose from waste palm fronds can be further processed into useful products and economic value, one of which is used as raw material for making oxalic acid. The purpose of this research is assess the effect of temperature and reaction time in the hydrolysis of palm fronds with alkali fusion method of producing oxalic acid. The research consisted of two stages that is the stage of preparation of palm fronds and the stage of oxalic acid synthesis, which include alkali fusion and crystallization processes. Analysis of the raw materials include the analysis of water content and cellulose content of palm fronds. From the results of this study showed water content is 53.7% and cellulose content is 30.9%. At this research for quantitative analysis includes the conversion of cellulose and yield oxalic acid. From these results obtained optimum conditions at a reaction temperature of 90 °C and a reaction time of 60 minutes the cellulosic conversion is 79.2% and a yield is 59.6% oxalic acid. For qualitative analysis includes purity analysis using FTIR and melting point analysis. FTIR analysis results indicate that the group has approached the standard of oxalic acid and melting point of 101.8 °C which indicates that the oxalic acid is obtained in the form of oxalic acid dihydrate.